The Impact of Implementation Contemporary Art Practices into Art Education on the Artistic Development of Eighth-Grade Students - Kozjek Varl, Katja; Herzog, Jerneja (Revija za elementarno izobraževanje, 2025)
It is known that several factors can have a positive effect on the artistic development of pupils, but it has not yet been investigated whether such development can also be positively influenced by the contemporary visual arts. Mainly because it is multi-layered and complex to understand, the question here is whether teachers can incorporate contemporary visual arts to the same degree and extent as other visual arts content to exert a positive influence on the development of artistic skills. Therefore, in this paper we present the results of a pedagogical experiment conducted to examine the effects of incorporating contemporary artistic practices on the development of artistic creativity skills in eighth graders (N = 121). Through the study, we were able to demonstrate that the inclusion of contemporary art practices in art lessons does have a positive impact on the development of art design skills among eighth graders.
Keywords: contemporary visual arts, art instruction, art development, artistic design skills.